THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL CONFIDENCE, AND INCOME ON FINANCIAL BEHAVIOR AMONG THE WORKFORCE IN JAKARTA - Agus Zainul Arifin (MIX: Jurnal Ilmiah Manajemen, 2017)
Abstract. The purpose of this study is to analyze the influence of financial knowledge, financial confidence and income, on financial behavior. This research is based on TPB Model and Behavioral Finance Theory, and it was carried out based on the phenomenon that occur at present whereas the community is more focused on shortterm rather than on long-term. The Theory of Planned Behavior that rates the knowledge, self-confidence, and income becomes the basis of financial behavior of individuals, which become the topic of this research. The subjects in this study are the people of Jakarta Special Region, which includes the group of workforce who have already had the job and fixed income every month. The results of this research show that Financial Knowledge and Financial Confidence do affect Financial Behavior, whereas Income does not appear in the same way. Keywords: Financial Behavior, Financial Knowledge, Financial Confidence, Income